The manifestations of Filipina brides’ perceptions of femininity in the design of their wedding dresses - Camacho, Dense Clare E. (Colleg eof Home Economics, University of the Philippines Diliman, 2023)
Filipino weddings and wedding gowns have been largely shaped by Catholicism since the Spanish colonial era (Xenos & Cabamalan, 2007; Oxales, 2014). However, as an evolving, modernized Filipina femininity has recently emerged, the Filipino wedding dress may have been affected. Thus, this research aimed to describe how Filipina brides’ perceptions of femininity manifests in the wedding dress. This study was a multiple case study that used a descriptive research design and convenience sampling. The researcher interviewed twenty participants individually and collected qualitative data. A photograph analysis was conducted on each participant’s wedding dress. The researcher used two matrices to organize the data gathered. One to identify the garment details of each participant, and another to analyze the most common garment details among the participants. Thematic analysis was used to identify five themes: (1) expression of sexual moderation and respectability, (2) role of the woman, (3) conforming to beauty standards, (4) conforming to tradition, and (5) the influence of religion. It was found that while participants held a generally traditional and culturally Filipino view on femininity, they also recognized modernity and tradition’s coexistence within a woman. This reflected in their wedding dresses, which despite displaying certain modern styles, still conformed to traditional social conventions. The researcher recommends expanding the study to include brides over 34 years old and those residing outside Metro Manila, non-Catholic and non-Christian weddings and those held outside the Philippines, and RTW or pre-owned gowns, in order to gain a more holistic view of Philippine weddings.